2019
DOI: 10.4103/ajm.ajm_3_19
|View full text |Cite
|
Sign up to set email alerts
|

Gemella endocarditis: A case report and a review of the literature

Abstract: Infective endocarditis (IE) remains a prevalent disease with a high rate of morbidity and mortality. Recent changes have been noted in the profile of causative microorganisms. In this report, we describe a case of Gemella-related endocarditis and review the related literature. Our patient was an 81-year-old man who presented with dyspnea and fatigue. His initial examination revealed a new systolic murmur. Echocardiogram revealed moderate mitral regurgitation with 1-cm mass on the anterior mitral leaflet, and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(56 citation statements)
references
References 32 publications
(48 reference statements)
0
40
0
Order By: Relevance
“…oralis AsaA as a query. AsaA orthologues were identified in other IE-causing bacterial species including S. mitis, Staphylococcus pasteuri, Granulicatella elegans and G. haemolysans [43][44][45][46][47][48][49][50][51][52][53]. Overall, the protein architecture of these AsaA orthologues is similar to that of S. oralis AsaA.…”
Section: Asaa Is Present In Other Ie-causing Bacterial Speciesmentioning
confidence: 81%
See 1 more Smart Citation
“…oralis AsaA as a query. AsaA orthologues were identified in other IE-causing bacterial species including S. mitis, Staphylococcus pasteuri, Granulicatella elegans and G. haemolysans [43][44][45][46][47][48][49][50][51][52][53]. Overall, the protein architecture of these AsaA orthologues is similar to that of S. oralis AsaA.…”
Section: Asaa Is Present In Other Ie-causing Bacterial Speciesmentioning
confidence: 81%
“…AsaA orthologues were identified in other IE-causing species including G. haemolysans, G. elegans, S. pasteuri and S. mitis [43,45,46,50,51]. Although the overall architecture of these proteins is similar, some display differences in the domains present in the NRR and the number of DUF1542 repeats.…”
Section: Discussionmentioning
confidence: 99%
“…pasteuri and S . mitis [ 45 , 47 , 48 , 52 , 53 ]. A previous study identified DUF1542-containing proteins in five S .…”
Section: Discussionmentioning
confidence: 99%
“…A recent review of literature suggested that G. morbillorum is the most common species associated with endocarditis and mitral valve is the most common heart valve involved. Onset of illness was subacute in most cases and fever was the most common presenting complaint [ 7 ]. Predisposing factors for endocarditis include dental infections and procedures, colon malignancies or gastrointestinal diagnostic procedures, immunosuppression, and preexisting cardiac abnormalities [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Inherent resistance to TMP-SMX and low-level resistance to aminoglycosides has been reported [ 9 ]. Aminoglycosides have been used in combination with beta lactams especially aqueous crystalline penicillin G and ampicillin for synergy and currently this combination is considered the treatment of choice [ 3 , 7 , 11 ]. Intravenous vancomycin can be used in patients with beta lactam allergy.…”
Section: Discussionmentioning
confidence: 99%